Improve the Quality of Life of Elderly Through Family Role - Sincihu, Yudhiakuari; Maramis, W F; Rezki, Muhammad Nur (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2018)
Every human is getting old and we must attempt to be happy in the old time. The problem is 17.5% of elderly people have poor quality of life and 62.5% are sufficient. Elderly at this level needs immediate intervention because it will be a burden for families. communities and governments. This study aims to analyze the family participation on improving the quality of life. An observational study with cross sectional approach with population study at Posyandu Lansia Mekar Sari Surabaya. We used purposive sampling method. We took 54 samples elderly aged ≥ 60 years out of 96 elderly who enrolled in Posyandu year 2016. Data were obtained from WHOQoL-BREF and family role questionnaire. We analyzed the data with Rank Spearman’s Correlation. There was a positive correlation between the family role and the quality of life (p=0.000.. r=0.568). mainly by environmental domain (p=0.000. r=0.561). psychological domain (p=0.008. r=0.358). and social relations domain (p=0.011. r=0.345). but not for physical domain (p=0.154. r=0.917). The family participation such as adaptation. partnership. growth. affection. and resolve could be one method to improve the quality of life of elderly. Every increasing family value would add up to 26.3-43.2% assessment the quality of life.